2016
DOI: 10.1093/nar/gkw709
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian PNLDC1 is a novel poly(A) specific exonuclease with discrete expression during early development

Abstract: PNLDC1 is a homologue of poly(A) specific ribonuclease (PARN), a known deadenylase with additional role in processing of non-coding RNAs. Both enzymes were reported recently to participate in piRNA biogenesis in silkworm and C. elegans, respectively. To get insights on the role of mammalian PNLDC1, we characterized the human and mouse enzymes. PNLDC1 shows limited conservation compared to PARN and represents an evolutionary related but distinct group of enzymes. It is expressed specifically in mouse embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 54 publications
3
30
1
2
Order By: Relevance
“…We propose that in bovine oocytes, TDRKH is also important for PIWIL3 recruitment to mitochondria since PIWIL3 physically interacts with TDRKH and co-localizes with TDRKH on the mitochondria. This TDRKH binding brings the piRNA-bound PIWIL3 in close proximity to PNLDC1, a deadenylase responsible for the elimination of mRNA 3’ poly(A) tails and trimming during pre-pachytene and pachytene pre-piRNA maturation 25,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…We propose that in bovine oocytes, TDRKH is also important for PIWIL3 recruitment to mitochondria since PIWIL3 physically interacts with TDRKH and co-localizes with TDRKH on the mitochondria. This TDRKH binding brings the piRNA-bound PIWIL3 in close proximity to PNLDC1, a deadenylase responsible for the elimination of mRNA 3’ poly(A) tails and trimming during pre-pachytene and pachytene pre-piRNA maturation 25,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…2). The unique domains of each protein likely mediate subcellular localization, substrate, and regulatory partner specificity, as has been observed for CAF1z [30,35,36], PDE12 [3739], PARN [36,4042], and PNLDC1 [4346]. NOCT biological function is likely further defined by its expression pattern and subcellular localization.
10.1080/15476286.2018.1526541-F0002Figure 2.NOCT is related to CCR4-type deadenylases and contains a conserved EEP catalytic domain.
…”
Section: Post-transcriptional Control Of Mrna Abundance and Stabilitymentioning
confidence: 99%
“…Several deadenylases exhibit specific subcellular distribution [35,3638,4043], raising the question of whether NOCT activity may be spatially restricted. Studies of overexpressed tagged constructs found Xenopus NOCT to be cytoplasmic in photoreceptor cells [95], while mouse NOCT is perinuclear in human HEK293 cells [57] and is excluded from stress granules in mouse NIH3T3 cells [56].…”
Section: Is Noct Activity Spatially Restricted?mentioning
confidence: 99%
“…Mass spectrometric analysis of protein components within the Papi complex immunoprecipiated from the cultured Bombyx cells led to the identification of a homolog of PNLDC1, termed Trim, as the piRNA 3′ processing factor (Figure B) . Trim is composed of CAF1 family ribonuclease and TM domains (Table ) through which it is localized on the mitochondrial surface, as is Papi.…”
Section: Bombyx Pirna Factors and Their Functionsmentioning
confidence: 99%